Pharmacological Activities of Ficus racemosa and Analysis of Its Major Bioactive Polyphenols by HPLC-DAD - Salma Akter Sumi; Md. Afjalus Siraj; Amir Hossain; Md. Sagir Mia; Seagufta Afrin; Md. Mustafizur Rahman (Highlights on Medicine and Medical Science Vol. 5, 2021)
Objective: Oxidative stress leads to numerous physiological disorders including infectious diseases, inflammation, and cancer. The present study was carried out to investigate antioxidant, antibacterial, and cytotoxic activity of methanol crude extract of leaves and fruits of the Ficus racemosa (LCME and FCME, resp.) and to analyse its major bioactive polyphenols by HPLC-DAD. F. racemosa has various uses in traditional medicine in the subcontinent for treating an array of diseases. Methods: Antioxidant capacity of the extracts was evaluated by DPPH free radical scavenging, reducing power, total phenolic, total flavonoid, total tannin content assay, superoxide radical, hydroxyl radical, and hydrogen peroxide scavenging assay. Identification and quantification of bioactive polyphenols were done by HPLC-DAD method. Antibacterial activity was tested by “disc diffusion” method. Brine shrimp lethality assay was carried out to check the cytotoxic potential. Results: Both LCME and FCME showed DPPH scavenging ability and concentration dependent reducing power activity. They had phenolic content, flavonoid content, and tannin content. Both the extracts showed superoxide radical scavenging ability, hydroxyl radical scavenging ability, and hydrogen peroxide scavenging ability. HPLC analysis of LCME and FCME indicated the presence of significant amount of gallic acid along with other phenolic constituents. Conclusion: Significant amount of gallic acid along with other phenolic constituents might have played an important role in the observed antioxidant, antibacterial, and cytotoxic activity.